2015
DOI: 10.1088/0004-637x/815/2/93
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of the Young Stellar Clusters in the Star-Forming Galaxy NGC 628

Abstract: We present a study of the spatial distribution of the stellar cluster populations in the star forming galaxy NGC 628. Using Hubble Space Telescope broad band WFC3/UVIS UV and optical images from the Treasury Program LEGUS (Legacy ExtraGalactic UV Survey), we have identified 1392 potential young ( 100 Myr) stellar clusters within the galaxy, identified from a combination of visual inspection and automatic selection. We investigate the clustering of these young stellar clusters and quantify the strength and chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 71 publications
(96 reference statements)
9
96
0
Order By: Relevance
“…The largest galaxy of the M74 galaxy group with an angular size of 10 5 × 9 5, a central and east pointing were obtained. The clustering of the young stellar clusters in this galaxy was investigated in an earlier paper by Grasha et al (2015), where an age dependency for the clustering strength was found with a randomization timescale of ∼40Myr, after which the clusters displayed a flatter, more homogeneous distribution.…”
Section: Ngc 628mentioning
confidence: 96%
See 4 more Smart Citations
“…The largest galaxy of the M74 galaxy group with an angular size of 10 5 × 9 5, a central and east pointing were obtained. The clustering of the young stellar clusters in this galaxy was investigated in an earlier paper by Grasha et al (2015), where an age dependency for the clustering strength was found with a randomization timescale of ∼40Myr, after which the clusters displayed a flatter, more homogeneous distribution.…”
Section: Ngc 628mentioning
confidence: 96%
“…A notable feature is the flat or decreasing distribution toward larger ages, especially visible in the class 3 associations, consistent with cluster disruption on timescales of a few tens of Myr or less; cluster fading can compound this effect as well. The class 3 population does behave distinctly differently compared to class 1 and 2 clusters: in addition to a decrease in their numbers at ages older than a few 10 Myr, their clustering properties in NGC 628 behave quite differently than class 1 and 2 clusters (Grasha et al 2015), and their disruption rate is significantly higher compared to class 1 and 2 clusters (Adamo et al 2017). Thus, we maintain that the class 3 associations represent a distinct type of system and appear to be born with lower densities than class 1 and 2 clusters and are not the remnants of dispersed/disrupted class 1 or 2 clusters.…”
Section: Cluster Identification Selection and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations